The sixtieth anniversary of the Polish Anthropological Society - Andrzej, Malinowski (Anthropological Review, 1986)
The article discusses the history of the Polish Anthropological Society. The development of anthropology which took place in Poland at the turn of the 19th century, particularly the activity of Józef Majer and Izydor Kopernicki contributed to the development of numerous Chairs of Anthropology at Universities. The second trend of the development of this science was the activity of the Polish emigrants, particularly in France. On their initiative, already in 1878 in Paris, a Polish Anthropological and Ethnografical Society was established with which Teofil Chudziński was associated. After the first world war anthropological institutions were created at universities which were staffed by known researchers like Jan Czekanowski (Lvov), Kazimierz Stolyhwo, Edward Loth, Jan Mydlarski (Warsaw), Julian Talko-Hryncewicz (Cracow), Michal Reicher (Vilna) and Adam Wrzosek (Poznań). The idea to create the Anthropological Society and its organ which was the "Anthropological Review" was the work of Adam Wrzosek who saw the necessity to integrate the rather scientifically differentiated anthropological circle. The Society was created in 1925 in Poznań and here were its Headquarters until the second world war. The Presidents of the Society were successively: A. Wrzosek, M. Ćwirko-Godycki, J. Mydlarski, T. Dzierżykray-Rogalski and at present this position is held by A. Malinowski. The Society integrates the Polish anthropology by its publications and the organization of scientific congresses and conferences.